Lateral diffusion of the PH-20 protein on guinea pig sperm: evidence that barriers to diffusion maintain plasma membrane domains in mammalian sperm (The Rockefeller University Press, 1987)
PH-20 protein on the plasma membrane (PH-20PM) is restricted to the posterior head of acrosome-intact guinea pig sperm. During the exocytotic acrosome reaction the inner acrosomal membrane (IAM) becomes continuous with the posterior head plasma membrane, and PH-20PM migrates to the IAM. There it joins a second population of PH-20 protein localized to this region of the acrosomal membrane (PH-20AM) (Cowan, A.E., P. Primakoff, and D.G. Myles, 1986, J. Cell Biol. 103:1289-1297). To investigate how the localized distributions of PH-20 protein are maintained, the lateral mobility of PH-20 protein on these different membrane domains was determined using fluorescence redistribution after photobleaching. PH-20PM on the posterior head of acrosome-intact sperm was found to be mobile, with a diffusion coefficient and percent recovery typical of integral membrane proteins (D = 1.8 X 10(-10) cm2/s; %R = 73). This value of D was some 50-fold lower than that found for the lipid probe 1,1-ditetradecyl 3,3,3',3'- tetramethylindocarbocyanine perchlorate (C14diI) in the same region (D = 8.9 X 10(-9) cm2/s). After migration to the IAM of acrosome-reacted sperm, this same population of molecules (PH-20PM) exhibited a 30-fold increase in diffusion rate (D = 4.9 X 10(-9) cm2/s; %R = 78). This rate was similar to diffusion of the lipid probe C14diI in the IAM (D = 5.4 X 10(-9) cm2/s). The finding of free diffusion of PH-20PM in the IAM of acrosome-reacted sperm supports the proposal that PH-20 is maintained within the IAM by a barrier to diffusion at the domain boundary. The slower diffusion of PH-20PM on the posterior head of acrosome-intact sperm is also consistent with localization by barriers to diffusion, but does not rule out alternative mechanisms.